2008
DOI: 10.1128/aac.00856-07
|View full text |Cite
|
Sign up to set email alerts
|

Differential Activities of Newer Antifungal Agents against Candida albicans and Candida parapsilosis Biofilms

Abstract: The activities of voriconazole, posaconazole, caspofungin, and anidulafungin against Candida albicans and Candida parapsilosis biofilms were evaluated. In contrast to planktonic cells, the MICs for voriconazole and posaconazole for the biofilms of the two species were high (>256 and >64 mg/liter, respectively) but relatively low for the echinocandins caspofungin and anidulafungin (<1 and <2 mg/liter, respectively).Candida spp. have frequently been associated with the formation of biofilms on biological and ine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
85
3
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(103 citation statements)
references
References 16 publications
10
85
3
5
Order By: Relevance
“…Similarly to our study, the data of Jacobson et al (2008) showed the SMIC 50 for anidulafungin to be ¡0.03125 mg ml 21 in 28 of 30 C. albicans clinical isolates tested when the biofilm was formed in RPMI 1640 medium. In contrast to the work of Katragkou et al (2008), we did not observe any indication of paradoxical growth during caspofungin activity against a mature C. albicans biofilm, even when high concentrations (4-8 mg ml 21 ) of the drug were administered to biofilms (data not shown). C. glabrata cells forming mature biofilm were less susceptible than the diploid species to caspofungin and anidulafungin in both media tested, albeit with up to half the thickness of C. albicans biofilms.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Similarly to our study, the data of Jacobson et al (2008) showed the SMIC 50 for anidulafungin to be ¡0.03125 mg ml 21 in 28 of 30 C. albicans clinical isolates tested when the biofilm was formed in RPMI 1640 medium. In contrast to the work of Katragkou et al (2008), we did not observe any indication of paradoxical growth during caspofungin activity against a mature C. albicans biofilm, even when high concentrations (4-8 mg ml 21 ) of the drug were administered to biofilms (data not shown). C. glabrata cells forming mature biofilm were less susceptible than the diploid species to caspofungin and anidulafungin in both media tested, albeit with up to half the thickness of C. albicans biofilms.…”
Section: Discussioncontrasting
confidence: 52%
“…However, caspofungin and anidulafungin were shown to have activity on mature C. albicans biofilms in vitro (Katragkou et al, 2008;Pemán et al, 2008) and in vivo (Shuford et al, 2006;Kucharíková et al, 2010a). Caspofungin was also shown to be active against mature C. glabrata biofilms formed in vitro (Choi et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…21,2008 CANDIDA PARAPSILOSIS 615 on May 11, 2018 by guest http://cmr.asm.org/ resistant as C. albicans biofilm to conventional antifungals, such as amphotericin B and azole compounds, (131,238). However, therapeutic levels of echinocandins can inhibit metabolic activities of C. parapsilosis biofilms (50,131,146), and lipid formulations of amphotericin B have shown activity against C. parapsilosis biofilm (146). Farnesol is a quorum-sensing agent in C. albicans that inhibits biofilm formation as well as filamentation (115,225).…”
Section: Biofilm Formationmentioning
confidence: 99%
“…Upon contact with various surfaces, C. albicans is known to form biofilms, which are a cause of infections associated with medical devices such as indwelling intravascular catheters. Those infections are particularly serious because biofilm-associated Candida cells display increased tolerance to a wide spectrum of antifungal drugs, including various azoles, such as fluconazole (MIC 50 ¢256 mg l 21 ) and miconazole (MIC 50 ¢256 mg l 21 ), and the newer generation of azoles, such as voriconazole (MIC 50 ¢256 mg l 21 ) and posaconazole (MIC 50 ¢64 mg l 21 ) (Lamfon et al, 2004;Ramage et al, 2009;Katragkou et al, 2008). Miconazole has moderate fungicidal activity against C. albicans biofilms, as 1-10 % sessile C. albicans cells can survive exposure to high doses (2080 mg l 21 ) of miconazole (Vandenbosch et al, 2010).…”
Section: Introductionmentioning
confidence: 99%